Implementasi Model ASSURE dalam Perencanaan Pembelajaran TIK di SMP Muallimin NU Pandan, Tapanuli Tengah : Implementation of the ASSURE Model in ICT Learning Planning at SMP Muallimin NU Pandan - Muhammad Arifin; Indra Pilianti Dongoran; Delismasari Delismasari; Fitri Malyani; Nadra Amalia (ITScience (Information Technology and Science), 2024)
Integrating information and communication technology (ICT)-based learning is necessary to develop students' high-level thinking skills, develop ICT skills (ICT Literacy), increase the effectiveness and efficiency, and bring out the attractiveness of the learning process. This article aims to analyze the impact of ICT use at SMP Muallimin NU Pandan. This study uses a qualitative descriptive method, and describing the ASSURE model can add variety to learning. Data was collected through observation, interviews, and document analysis. Implementing the ASSURE Model in ICT Learning Planning describes the readiness of learning teachers as an effort to increase motivation in learning participation, facilitate collaboration, and strengthen understanding of ICT skills. However, with limited resources, teacher and student abilities should be considered. The design of ASSURE-based learning with the stages of analyzing student characteristics and learning styles, choosing methods, media, and teaching materials, and actively involving students can create various learning innovations that are by student needs and improve teacher professional competence, especially pedagogical competence, namely utilizing ICT for learning purposes and teacher professional competence utilizing ICT for communication and self-development.